Use of computational methods in the study of chemical reactions of psychedelics and interstellar molecules: N,N-dimethyltryptamine and propargylimine - Coutinho, Lucas Pinheiro (2023)
Computational methods can be used to study chemical systems in order to give a myriad of insights about reaction mechanisms. From electron density based methods to molecular mechanic ones. Nonetheless, theoretical chemistry is at the state-of-the-art of current chemistry endeavour. Therefore, the present study, brings together two essays which exemplifies computational chemistry as a tool to modern chemistry: mechanistic insights of the biosynthesis of the psychedelic N,N-dimethyltryptamine (DMT) and the interstellar medium (ISM) molecule propargylimine (PGIM). In Chapter I, DMT, an endogenously human psychoactive product, is part of the L-tryptophan pathway, divided into the decarboxylation by an aromatic L-amino acid decarboxylase (AADC) for tryptamine formation (elucidated step) and the subsequent double-methylation by the indolethylamine-N-methyltransferase (INMT) through the cofactor S-adenosyl-L-methionine (SAM) (not elucidated step). Therefore, an in silico model, using ONIOM QM:MM calculations, was proposed based on the build S_N 2 potential energy surface (PES) profile, showing the second methylation energy barrier being the rate-limiting step with δG^‡=14.65 kcal∙mol^(-1) larger than the previous methylation. Besides, hybridization states of each reaction step were examined to follow geometry change along the reaction coordinate. In Chapter II, PGIM, an imine interstellar complex organic molecule (iCOM), is investigated, following a Strecker-type synthesis model, with a two-step mechanism: condensation of propynal and ammonia and a subsequent elimination of water molecule forming PGIM. The built PES was performed with wB97XD/aug-ccp-VTZ level of theory, in gas phase medium at temperatures of 10 and 298 K, showing the second energy barrier to be the rate-limiting step in both temperatures. Additionally, Quantum theory of atoms in molecules (QTAIM) calculations were done to analyse the obtained electron density and the hybridization states of the transition states were used to understand the geometrical of the energy barriers.